Fructose and Urea as Precursors for N‐/O‐Modified Mesoporous Carbon with Enhanced Sorption Capacity for Heavy Metal Ions. Issue 17 (19th May 2014) - Weinberger, Christian; Haffer, Stefanie; Wagner, Thorsten; Tiemann, Michael
Abstract: Ordered mesoporous carbon with a high heteroatom (N, O) content was prepared by nanocasting from a melt of a eutectic mixture of fructose and urea (60/40 wt.‐%; melting temperature ca. 65 °C). These precursor compounds are cheap and environmentally friendly. The material possesses enhanced pore‐wall surface polarity as compared to that of mesoporous carbon prepared by the same technique without urea. This was verified by water sorption analysis. As a result, the heteroatom‐modified material shows higher sorption capacity for the uptake of heavy metal ions (Cu 2+ ) from aqueous solution, which may be interesting for potential application in wastewater cleaning. Abstract : Ordered mesoporous carbon with a high heteroatom (N, O) content is prepared by nanocasting from a melt of a eutectic mixture of fructose and urea as cheap and environmentally friendly precursors. The material possesses enhanced pore‐wall surface polarity and high sorption capacity for heavy metal ions (Cu 2+ ) from aqueous solution.